PENGARUH FAKTOR-FAKTOR KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. BESS FINANCE - Harlan, Pandu Andre; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2014)
In Indonesia, nowadays service sector grown very fast and make contribution as 2/3 from all activities.  Service quality has strong relationship with customer satisfaction because customer satisfaction is the main key to build up service business especially leasing. So in this research will analyze factors that affecting customer satisfaction  in PT BESS Finance.            Sample used in this research are 100 respondents that being consumers in PT BESS Finance Semarang. Technique data used are multiple regression analysis with validity and reliability test, also the classic assumptions.This research will use multiple regression analysis. Based on the result and discussion, the conclusion are: (1) Significance value of information variable toward customer satisfaction is 0.033 < 0.05, this means information has significant effect toward customer satisfaction. (2) Significance value of hospitality variable toward customer satisfaction is 0.000 < 0.05, this means hospitality has significant effect toward customer satisfaction. (3) Significance value of caretaking variable toward customer satisfaction is 0.014 < 0.05, this means caretaking has significant effect toward customer satisfaction. (4)Significance value of billing variable toward customer satisfaction is 0.000 < 0.05, this means billing has significant effect toward customer satisfaction. (5)Significance value of payment variable toward customer satisfaction is 0.017 < 0.05, this means billing has significant effect toward customer satisfaction.